Can microsavings work without microcredit? A case study of India Post Payments Bank. (4th May 2020) - Ashta, Arvind; Pillarisetti, Satish
Abstract: Microsavings institutions that cannot provide microcredit are unlikely to be self‐sustaining. Payments banks are Indian microfinance institutions that can collect microsavings, but cannot give microcredit. They have been mainly unsuccessful owing to low spreads between interest given to savers and interest received from the reserve bank or commercial banks on interbank deposits. The commission income from transfer payments is too low to pay the high overheads of rural outreach. Payments banks would like to transform themselves into small savings banks that can provide microcredit.